Primary medical carein the regional healthcare system: problems of balance and accessibility - Melnyk, Alla; Shabaga, Andriy (Herald of Economics, 2025)
Introduction. Changes in the healthcare system in Ukraine are combined with the reform of the territorial management system. Special attention is paid to the organization of primary health care (PHC) provision to their residents. New challenges for entities responsible for the provision of PHC have arisen in connection with the formation of hospital clusters, the expansion of the list of medical services provided at the primary level. Insufficient scientific study of these transformational changes has determined the relevance of the research topic. The purpose of the study is to develop theoretical and methodological provisions and develop scientific and practical recommendations to improve the provision of primary health care to the population in the regions, taking into account modern challenges and unresolved problems.Methods. Statistical analysis methods, expert assessment method, focus group method, system analysis, comparative analysis, graphic methods were used to visually present the results of analytical research.Results. The article outlines the main transformational changes in the organization of PHC in the regions, the essential characteristics of the newly formed PHC model, changes in its philosophy in territorial communities and in financing principles. A systematic and comparative analysis was carried out: of the institutional basis of the organization of PHC, infrastructure support, forms of organization tested in the process of decentralization, the effectiveness of functional activities by demographic characteristics. An assessment was made of: the availability of medical services, logistical, financial, and personnel support. A comparative analysis of PHC for the population of two regions of Ukraine -Transcarpathian and Ternopil regions - was carried out. The reasons for the differences and critical issues that require joint solutions by public authorities, medical institutions as providers of medical services, market infrastructure institutions, etc. have been identified. Strategic priorities have been identified and mechanisms for improving the organization of PMD have been proposed.Prospects. The problems of implementing rehabilitation programs in the practice of PHC, including military ones, as well as the organizational aspects of the interaction of PHC institutions with the system of specialized medical care, are considered promising for research.